Comparative life cycle assessment of power-to-gas generation of hydrogen with a dynamic emissions factor for fuel cell vehicles. (December 2015) - Walker, Sean B.; Fowler, Michael; Ahmadi, Leila
Highlights: P2G effective to generate clean hydrogen for fuel cell vehicles. P2G excellent payback when paired with Ontario cap-and-trade. Dynamic emissions factor allows for cleaner H2 generation. Power generation emissions impact performance of green H2 . Abstract: Power-to-gas, an excellent energy storage technology, is also useful for the role it can play in producing hydrogen for fuel cell vehicles. The replacement of the existing transportation infrastructure and the end of society's reliance on carbon-based fuels is dependent on the development of efficient, cleaner technologies as well as 'smart energy networks'. One of the most touted technological advances is the replacement of internal combustion engines with 'green' hydrogen fuel cell vehicles. Hydrogen fuel cell vehicles do not emit any greenhouse gases or other emissions as such do not directly contribute to climate change or urban air pollution during their operation. With green hydrogen as the fuel, the emissions from the fuel production become dependent not on the vehicle type or electrolyzer technology, but on the sources of electricity being used to generate the hydrogen. In this study, the authors examine the use of electrolytic hydrogen to power vehicles and compare this with its internal combustion counterpoint. In this analysis a dynamic electrical grid emissions factor, based on the total grid mix of energy generation technologies at any given time, is determined. In this case study, the province of Ontario, Canada is used. Unique to this work is that the simulation of the generation of hydrogen is via electrolysis under different control strategies; the strategies considered, specifically, are continuous electrolyzer operation, price threshold operation, or operation based on an emission factor threshold based on the mix of energy generation technologies feeding the grid at any given hour. With the introduction of new policy tools to reduce greenhouse gas emissions, such as carbon taxes and cap-and-trade, the monetization of emissions provides an even greater incentive for industry to reduce their greenhouse gas emissions. In this study, it is illustrated that by using the dynamic emissions factor to control the production of hydrogen, emissions can be significantly reduced over the life of the vehicle.